The Prevalence of Depression and Anxiety Among the University Graduates in Bangladesh: How Far Does it Affect the Society? - Ara, Esmat; Khan, Mohaiminul Islam (European Scientific Journal, ESJ, 2019)
The symptoms of anxiety and depression amongst university students are more common throughout the globe as it affects one’s social, economic, and academic life negatively. Although the students in developing and lowincome countries have more tendencies to experience depression and anxiety, the extent and pattern of the problem of depression are largely unknown. This paper focuses on exploring the various models of depression amongst recent graduates of Shahjalal University of Science & Technology, Sylhet- Bangladesh, who experienced depression and anxiety throughout their academic life. This is an exploratory study where in-depth interview methods have been used for the collection of data. This study involved field research, and it is based on the primary data and secondary data received from books, articles, newspapers, archival documents review, and other online sources to define concepts and relevant terms. Thematic analysis method has been employed through coding processes to analyze the collected data. The findings from this study revealed that most students, especially the female students, suffered from depression and anxiety in their academic life. This is most likely due to educational, social, personal, and family-related issues. This study also reveals a high tendency of suicide, involvement in illegal activities, and failure to attain academic goals amongst depressed students. Hopefully, from this research, these findings will provide some guidelines and policy strategies based on the nature of these problems. Also, it will serve as a guide for future researchers and academic and policymakers to base their reports on in order to reduce this social disease.